Comprehensibility and Prosody Ratings for Pronunciation Software Development - Paul Warren; Irina Elgort; David Crabbe (Language Learning and Technology, 2009)
In the context of a project developing software for pronunciation practice and feedback for Mandarin-speaking learners of English, a key issue is how to decide which features of pronunciation to focus on in giving feedback. We used naïve and experienced native speaker ratings of comprehensibility and nativeness to establish the key features affecting comprehensibility of the utterances of a group of Chinese learners of English. Native speaker raters assessed the comprehensibility of recorded utterances, pinpointed areas of difficulty and then rated for nativeness the same utterances, but after segmental information had been filtered out. The results show that prosodic information is important for comprehensibility, and that there are no significant differences between naïve and experienced raters on either comprehensibility or nativeness judgements. This suggests that naïve judgements are a useful and accessible source of data for identifying the parameters to be used in setting up automated feedback.